Full Field Digital Mammography (FFDM) versus CMOS Technology versus Tomosynthesis (DBT) – Which System Increases the Quality of Intraoperative Imaging? - Schulz-Wendtland, R.; Dilbat, G.; Bani, M.; Fasching, P. A.; Lux, M. P.; Wenkel, E.; Schwab, S.; Loehberg, C. R.; Jud, S. M.; Rauh, C.; Bayer, C. M.; Beckmann, M. W.; Uder, M.; Meier-Meitinger, M. (Geburtshilfe und Frauenheilkunde, 2012)
Aim: The aim of this prospective clinical study was to assess whether it would be possible to reduce the rate of re-excisions and improve the quality using CMOS technology or digital breast tomosynthesis (DBT) compared to a conventional FFDM system. Material and Methods: An invasive breast cancer (BI-RADS 5) was diagnosed in 200 patients in the period from 5/2011 to 1/2012. After histological verification, a breast-conserving therapy was performed with intraoperative imaging. Three different imaging systems were used: 1) Inspiration™ (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 µm pixel pitch, 8 l/mm as the standard; 2) BioVision™ (Bioptics, Tucson, USA), flat panel photodiode array, tungsten source, focus 0.05, resolution 50 µm pixel pitch, 12 l/mm; 3) Tomosynthesis (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 µm pixel pitch, 8 l/mm, range: 50°, 25 projections, scan time > 20 s, geometry: uniform scanning, reconstruction: filtered back projection. The 600 radiograms were prospectively shown to 3 radiologists. Results: Out of a total of 200 patients with histologically confirmed breast cancer (BI-RADS 6) 156 patients required no further operative therapy (re-excision) after breast-conserving therapy. A retrospective analysis (n = 44) showed an increase in sensitivity with tomosynthesis compared to the BioVision™ (CMOS technology) and the Inspiration™ at a magnification of 1.0 : 1.0 of 8 % (p < 0.05), i.e. re-excision would not have been necessary in 16 patients with tomosynthesis. Conclusions: The sensitivity of tomosynthesis for intraoperative radiography is significantly (p < 0.05) higher compared to both CMOS technology and an FFDM system with a conventional detector. Additional studies using higher magnification, e.g. 2.0 : 1.0, but no zooming will be necessary to evaluate the method further.
Keywords: breast; mammographic density; mammography; breast cancer